Green HR Practices: The Savior from Adverse Impacts of Global Warming: Managing environmental concerns through Green HR practices (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The nations and society today is well aware of the changes taking place in the environment on account of global warming. Since the historical industrial revolution, generations have been tampering the nature by virtue of non-environmental friendly practices caused by the pollution of land, water and air. The exponential rise in the population has further catastrophically mounted the pressure on the environment and the existence of future generations is at stake. Although there is an outcry today and universal realization for it, not much effort is being done in order to overcome the problem. The measures being adopted do not keep pace with the damage that has already been caused and that continues to be so.The major contributors to this environmental crisis have been the industry and especially the ones that have significant carbon prints. Until and unless, there is a widespread realization among all industries towards the problems of global warming caused by the environmental pollution, the regulatory bodies would not be successful in managing the issue. Since HR is the backbone of all organizations, Green HR practices can be the key to this massive problem. By incorporating Green HR practices, industry can significantly contribute to at least minimize the damage caused even if the problem is not uprooted.This paper endeavors to identify the potential environmental concerns that can be managed by efficient Green HR practices religiously adopted by committed organizations. The evolution of Green HR practices and its correlation in modern day context has also been elaborated upon. By adopting these measures, at least the first step towards environmental sustainability can be ensured.